Global democracy for sustaining global capitalism: the way to solve current global problems - "Andreu, Jose Miguel"; Rahman, Rita Dulci (New Delhi, 2009)
Providing a reasonable way out of the current global economic and political crisis, this study offers a comprehensive explanation of the foundations of this crisis as well as detailed criticisms of current solution measures, while showing a way to create long-lasting peace, human security, and a sustainable ecosystem for all. After carefully analyzing the foundations of democracy at national and global levels, the conditions for sustainability of democracy, and its interconnections with capitalism, the proposal suggests a complete redesign of the United Nations and its economic agencies to result in a global democracy for exclusively dealing with global public goods and externalities. A priority target of this suggested reorganization is a more balanced and acceptable global distribution of income, as a necessary condition for the survival of global capitalism.
Keywords: Globalization